TRANSFORMATION IN ARCHITECTURAL SOCIETIES BY NATURAL ADAPTATION AND DESIGN - Harsritanto, Bangun I. R (architecture department, Engineering faculty, Universitas Diponegoro, 2023)
On this Vol 23 no1, MODUL has published 7 scienteific articles and an event report. The event report had spotted the new regulation that will transform the architectural society, one concept of arsitektur nabati which offered as response of COVID, and the transformation by demand of people. With compiling the information of all published articles, this editorial try to provide a resume using theory by Loye and Aisler that identity the transformation and chaos.